Panama : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper assesses Panama's business model founded on its ability to attract international financial, business, and transportation services. Panama has had exceptional growth over recent decades. A growth diagnostic exercise suggests that Panama is well placed to maintain this business model. Higher-quality education, stronger governance, and less bureaucracy will further strengthen Panama's comparative advantage. Additional analysis suggests that investment will continue to support growth, while the logistics and tourism sectors promise to build further on Panama's comparative advantage.